Edible Insects - Mikkola, Heimo (IntechOpen, 2020)
Insect protein production through 'mini-livestock farming' has enormous potential to reduce the level of malnutrition in critical areas across the world. It has been estimated that insect eating is practised regularly by over two billion people, mostly in China and in most tropical countries in Africa, South America, and Asia. However, eating insects has been taboo in many western nations. Reasons for this are discussed in this book with examples from Finland and the UK. The enormous boom of insect farming in Finland started in September 2017 when the business type was legalized. However, a large part of the population found the insect food too expensive and exotic. UK research outlines a multitude of promising strategies to overcome 'western' resistance to eating insects. This book also includes a chapter on the potential of insect farming to increase global food security. It shows that Africa is a hotspot of edible insect biodiversity and there more than 500 species consumed daily. We have several examples of viable insect farming businesses that can fight poverty and malnutrition in developing countries and provide profit and wealth to rural farmers. The chapters of the book cover countries such as Cameroon, Ecuador, Finland, Ghana, India, Mexico, the UK, and the US.